Perbandingan Efektivitas Ferric Carboxymaltose Dengan Ferrous Sulfate Sebagai Terapi Pasien Anemia Defisiensi Besi Pada Wanita Hamil - Muhammad Nafi’ Rizqi Amanillah; Muhammad Shoim Dasuki; Sri Wahyu Basuki; Supanji Raharja (INVOLUSI: Jurnal Ilmu Kebidanan, 2021)
Background: Iron deficiency anemia is still a global problem, especially in pregnant women and causes maternal death due to bleeding. This is because the need for iron increases and the food supply decreases due to improper diet and nutritional patterns before pregnancy and during pregnancy. Iron supplements are an alternative in overcoming this problem, supplements are divided into two options, namely oral and parenteral. Objective: To compare the effectiveness of Ferric carboxymaltose with Ferrous sulfate as a treatment for iron deficiency anemia in pregnant women in terms of increased hemoglobin and ferritin levels. Method: Systematic Review, this research was sourced from online databases, namely: PubMed, Science direct, Garuda ristekbrin, Google scholar and Research gate with the keywords: ("iron deficiency anemia in pregnancy" OR "Anemia Pregnancy" OR "iron-deficient gravidas" ) AND ("Ferric carboxymaltose" OR "FCM" OR "iron dextri-maltose") AND ("Ferrous sulfate" OR "Ferrous Sulphate" OR "ammonium ferrous sulfate"). The data in this study were analyzed in a narrative manner with data extraction containing: name of journal, author, year, research design, sample and results with a search time limit of 2015-2020. Summary of results: this study found that Ferric carboxymaltose gave more improvement than Ferrous sulfate in terms of increasing hemoglobin and ferritin levels. Conclusion: The final result of this systematic review study is that Ferric carboxymaltose is more effective than Ferrous sulfate for the management of iron deficiency anemia in pregnant women in terms of increasing hemoglobin and ferritin levels.